2021
DOI: 10.21203/rs.3.rs-532419/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association between Triglyceride Glucose Index and the Risk of Peripheral Artery Disease

Abstract: Background The triglyceride glucose (TyG) index has been used as a simple surrogate marker of insulin resistance, an independent predictor of atherosclerotic vascular diseases. However, few studies have investigated the relationship between the TyG index and peripheral artery disease (PAD).Methods A total of 3375 participants with comleted TyG and ankle brachial pressure index (ABPI) records were enrolled from the National Health and Nutrition Examination Survey (NHANES) 1999-2004. The TyG index was calculated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…The TyG index plays a potential role in all stages of CAD, affects the formation of atherosclerotic plaques associated with coronary artery calcification and coronary artery stiffness, and can predict the degree of coronary artery stenosis [33,34]. In addition, it is an independent predictor of peripheral arterial disease and is related to IR, vascular inflammation, and stiffness that contribute to peripheral arterial atherosclerosis [35–37]. In our study, we found significantly higher coronary and pulmonary artery diseases in the nondipper group.…”
Section: Discussionmentioning
confidence: 55%
“…The TyG index plays a potential role in all stages of CAD, affects the formation of atherosclerotic plaques associated with coronary artery calcification and coronary artery stiffness, and can predict the degree of coronary artery stenosis [33,34]. In addition, it is an independent predictor of peripheral arterial disease and is related to IR, vascular inflammation, and stiffness that contribute to peripheral arterial atherosclerosis [35–37]. In our study, we found significantly higher coronary and pulmonary artery diseases in the nondipper group.…”
Section: Discussionmentioning
confidence: 55%